Crucial sequences within the Epstein-Barr virus TP1 promoter for EBNA2-mediated transactivation and interaction of EBNA2 with its responsive element. - Meitinger, C (1994)
EBNA2 is one of the few genes of Epstein-Barr virus which are necessary for immortalization of human primary B lymphocytes. The EBNA2 protein acts as a transcriptional activator of several viral and cellular genes. For the TP1 promoter, we have shown previously that an EBNA2-responsive element (EBNA2RE) between -258 and -177 relative to the TP1 RNA start site is necessary and sufficient for EBNA2-mediated transactivation and that it binds EBNA2 through a cellular factor. To define the critical cis elements within this region, we cloned EBNA2RE mutants in front of the TP1 minimal promoter fused to the reporter gene for luciferase. Transactivation by EBNA2 was tested by transfection of these mutants in the absence and presence of an EBNA2 expression vector into the established B-cell line BL41-P3HR-1. The analysis revealed that two identical 11-bp motifs and the region 3' of the second 11-bp motif are essential for transactivation by EBNA2. Methylation interference experiments indicated that the same cellular factor in the absence of EBNA2 binds either one (complex I) or both (complex III) 11-bp motifs with different affinities, giving rise to two different specific protein-DNA complexes within the left-hand 54 bp of EBNA2RE. A third specific complex was shown previously to be present only in EBNA2-expressing cells and to contain EBNA2. Analysis of this EBNA2-containing complex revealed the same protection pattern as for complex III, indicating that EBNA2 interacts with DNA through binding of the cellular protein to the 11-bp motifs. Mobility shift assays with the different mutants demonstrated that one 11-bp motif is sufficient for binding the cellular factor, whereas for binding of EBNA2 as well as for efficient transactivation by EBNA2, both 11-bp motifs are required.